Strategy of Student Management In Facing The Paradigm Shift In Education In The Digital Era: A Literature Review - Adzkia Ahmad, Abrar; Arindah, Putri; Robbaniyyah, Syifa; Nurwahidah, Salma Nisa (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2023)
In the ever-evolving digital era, changes in the educational paradigm demand effective student management strategies. This article is a literature review that discusses these strategies based on student perspectives, expert opinions, and relevant literature sources. The main focus of these strategies is the integration of technology into the curriculum, the development of teacher professionalism, collaboration with industry and communities, and the empowerment of students. By implementing these strategies, educational institutions can create adaptive, innovative, and relevant learning environments that keep up with the times. This approach provides a strong foundation for student development in tackling challenges and harnessing potential in the digital era.